Preoperative left atrial volume index may be associated with postoperative atrial fibrillation in non-cardiac surgery - Oh, Ah Ran; Lee, Sung Ho; Park, Jungchan; Lee, Jong-Hwan; Cha, Dahye; Yang, Kwangmo; Choi, Jin-Ho; Ahn, Joonghyun; Sung, Ji Dong; Choi, Bogeum; Lee, Seung-Hwa (Frontiers in Cardiovascular Medicine, 2022)
Background Postoperative atrial fibrillation (POAF) is related to mortality after non-cardiac surgery. Left atrial volume index (LAVI) is known to be associated with prognosis and development of atrial fibrillation, but it has not been fully investigated in patients undergoing non-cardiac surgery. Materials and methods A total of 203,787 consecutive adult patients underwent non-cardiac surgery at our institution between January 2011 and June 2019. After identifying those with available LAVI estimated during preoperative echocardiography, we divided them into those with LAVI higher and lower than 34 mL/m2. The primary outcome was incidence of POAF. Results A total of 83,097 patients were enrolled in this study. The study patients were divided into the low (57,838 [69.6%]) and high (25,259 [30.4%]) LAVI groups. After an adjustment, higher LAVI was associated with increased incidence of POAF (5.1% vs. 8.1%; odds ratio [OR], 1.33; 95% confidence interval [CI], 1.25–1.41; p < 0.001). In 24,549 pairs of propensity-score-matched population, the result was similar (6.2% vs. 7.9%; OR, 1.30; 95% CI, 1.21–1.39; p < 0.001). The estimated threshold of LAVI associated with POAF was 36.4 mL/m2 with an area under the curve of 0.571. Subgroup analysis in non-thoracic and thoracic surgery showed that the association between preoperative LAVI and POAF significantly interacted with diastolic dysfunction (p for interaction < 0.001), and the observed association was valid in patients without diastolic dysfunction. Conclusion Preoperative LAVI was shown to be associated with POAF in non-cardiac surgery. Our result needs verification in further studies.